2008
DOI: 10.1007/s00415-008-0008-6
|View full text |Cite|
|
Sign up to set email alerts
|

Bell’s palsy

Abstract: There is insufficient evidence concerning the efficacy of antiviral treatment of Bell's palsy (BP). We therefore compared the efficacy of prednisone and famciclovir to prednisone treatment alone in BP. A total of 167 consecutive patients with untreated acute BP were included. Severity of BP was evaluated using the House-Brackmann scale (HBS) and virus antibody tests (herpes simplex virus, varicella zoster virus) were performed. Patients admitted on even dates were treated with prednisone ("P group") and patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…A total of 574 patients who received steroids alone and 571 patients who received steroids and antivirals were included. Three studies used aciclovir as the antiviral,6 10 22 two studies used valaciclovir,12 14 and one study used famciclovir 9. Most of the included studies were of high quality (Jadad score ≥3) except for Minnerop et al,9 which was not blinded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 574 patients who received steroids alone and 571 patients who received steroids and antivirals were included. Three studies used aciclovir as the antiviral,6 10 22 two studies used valaciclovir,12 14 and one study used famciclovir 9. Most of the included studies were of high quality (Jadad score ≥3) except for Minnerop et al,9 which was not blinded.…”
Section: Resultsmentioning
confidence: 99%
“…There was one inter-reviewer disagreement during data extraction, which was resolved by a third independent reviewer. The Sullivan et al,6 the Minnerop et al,9 and the Adour et al22 studies did not report the necessary data regarding the groups of interest; the corresponding authors were contacted and kindly provided the necessary information.…”
Section: Methodsmentioning
confidence: 99%
“…Conflicting results were reported in different studies on the benefit of combining anti viral therapy with corticosteroid to achieve better outcome. Minnerop et al reported that combination of famciclovir and prednisone was superior to prednisone alone in cases of severe Bell's palsy [188]. Combining antiviral therapy with prednisone increase the recovery rate slightly but not significantly compared to prednisone monotherapy [189].…”
Section: Bell's Palsymentioning
confidence: 99%
“…In contrast, the meta-analysis by Quant et al. (2009) , including the study by Minnerop et al. (2008) but excluding those by Kawaguchi et al.…”
Section: Managementmentioning
confidence: 99%